Financial cybercrime avoidance behavior among employees of financial sector companies in Indonesia - Hanifah Zahra; Dekar Urumsah (The Indonesian Accounting Review, 2024)
This study aims to examine the factors that influence the behavior of avoiding financial cybercrime among employees of financial sector companies in Indonesia. This studyuses Technology Threat Avoidance Theory (TTAT) and Regret Theory as theoretical frameworks. Data are collected through a survey conducted onemployees of financial sector companies in Indonesia, both in paper-based and online formats, resulting in a total of 180 questionnaires for analyses. Data analysis is conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) in SmartPLS 4.0. The results of this study show thatperceived susceptibility and perceived severity have a significant positive influence on perceived threat. However, the interaction between perceived susceptibility and perceived severity has no effect on perceived threat. Perceived threat, safeguard effectiveness, and anticipated regret have a significant influence on financial cybercrime avoidance motivation. Conversely, self-efficacy and safeguard cost do not have an effect onfinancial cybercrime avoidance motivation. Furthermore, financial cybercrime avoidance motivation has a significant and positive influence on financial cybercrime avoidance behavior. These findings offer insights for policymakers, financial sector companies, and antivirus software developers to enhance cybersecurity policies, responses to cybercrime, and software features.